Preparación docente para la intervención en estudiantes con déficit de atención de educación general básica media - Guerrero Solís, Aliz Karina (2021)
The purpose of this qualification work is to offer the teacher the preparation through a teaching material that provides him with knowledge about Attention Deficit Disorder (TDA) and the appropriate forms for educational intervention from the teaching-learning process itself, in students suffering from this disorder in the A. Farina Educational Unit of Middle Basic General Education. In the research process, theoretical references were taken that contributed to the understanding of the pedagogical alternative and the importance of teaching preparation in educational intervention. With regard to the methodology used, part of the mixed approach with descriptive and correlal scope. Methods and tools were used to gather information, including the survey, observation sheets for teachers and students, and the sustained interview with the vicechancellor responsible for pedagogical management at the institution………